If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 3p + 2 = 20 Reorder the terms: 2 + 3p = 20 Solving 2 + 3p = 20 Solving for variable 'p'. Move all terms containing p to the left, all other terms to the right. Add '-2' to each side of the equation. 2 + -2 + 3p = 20 + -2 Combine like terms: 2 + -2 = 0 0 + 3p = 20 + -2 3p = 20 + -2 Combine like terms: 20 + -2 = 18 3p = 18 Divide each side by '3'. p = 6 Simplifying p = 6
| 3y-43z+6y+3=66.56y | | 9+6x+x=93 | | 134-4x=32x+22 | | 3a+10=19 | | 3y-5=5y+1 | | 4p^2+10p=0 | | 3x+11=-16 | | 5x+5=21 | | .5x=0.21428571428x+0.57142857142 | | =3x-5 | | x=0.5x^2 | | x=7y+25-0.5x | | 4x+55=3x+11 | | 5x-2=-62 | | x+4y= 48 | | x=650+0.7x^2 | | -3y+4y=80 | | .75(5x+2)=3(4-3x)+15 | | 7y-9=3y+13 | | 6x+17=59 | | 26x+21=-39x-10 | | 9x+4y= | | 52-4x=14x+18 | | 2(4x+5)=2(x+4) | | 9-8x=49-36x | | 100-5x^2=0 | | -4.5+y=-12.3 | | 162-6x=21x+15 | | 2x+9=-61-8x | | 133-3x=24x+22 | | x^2-23x=0 | | 2.3-n-4n=-32 |